TINJAUAN INTRINSIK DUA LAKON DRAMA KONVENSIONAL DAN INKONVENSIONAL PUTU WIJAYA: BILA MALAM BERTAMBAH MALAM DAN EDAN - Dapy Fajar Raharjo (Balai Bahasa Kalimantan Tengah, 2018)
The result of research shows that Putu Wijaya has been done reformer in writing play drama, that is conventional form become inconventional form. The reformer that Putu Wijaya done in writing play drama can be identified 1) conventional plot commonly linear and intimate, while inconventional plot is random or loose; 2) conventional plot depend on the development of problem and conflict, while inconventional plot problem show and gone without solution; 3) conventional dialog drama is reformed from dialog to show individual character player become dialog that express group character; 4) conventional drama individu player express certain individu character, while inconventional drama player express certain group character; 5) conventional drama have explicit identity and show certain character, while inconventional player known as sociology and physiology identity; and 6) conventional player character so influence the beauty player structure, while inconventional player character the player can’t be growth following the plot.